PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA NEGERI 2 MUARA BELITI TAHUN PELAJARAN 2015/2016 - Ovilia Putri Utami Gumay; Ety Kodarsih; Budi Mulyanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This thesis entitled â€œThe Effect of Learning ModelCooperatif Tipe Student Teams Achievement Division (STAD) to the Physics Learning Outcomes Seventh Grade Students of SMA Negeri 2 Muara Beliti Academic Year 2015/2016â€. The purpose of this study was to determine the effect of learning model cooperatif tipe student teams achievement division (STAD) on learning outcomes physics class X student of SMA Negeri 2 Muara Beliti academic year 2015/2016. This research is a quantitative research method experiments carried out in the presence of a comparison group pretest posttest design group design. As the population is all students of class X SMA 2 Muara Beliti academic year 2015/2016 , consisting of 216 and a sample is first class and the experimental class X.3 graders X.8 as the control class. The samples in this study were randomized (random sampling) by means of the draw. The data collection was done by using the test . The collected data were analyzed using t-test. Based on the results of t-test analysis at significance level a = 0.05, obtained t (7,83) > t table (1.67). It can be concluded that there is significant influence learning model Cooperatif Tipe Student Teams Achievement Division (STAD) on learning outcomes physics class X student of SMA Negeri 2 Muara Beliti academic year 2015/2016. Keywords : Make A Match, learning outcomes.